Infertility due to salpingitis: demographic and clinical characteristic in patients attendend at Arzobispo Loayza Hospital - Cansino, Raquel (2015)
OBJECTIVE: To determine demographic and clinical characteristics of patients with infertility due to salpingitis. SETTING: Arzobispo Loayza Hospital, from January through June 2001. MATERIAL AND METODOS: Review of clinical registries of 77 patients with infertility due to salpingitis. RESULTS: Fifty-two patients (67%) were between 30 and 39 year-old; 54 (70%) began sexual relations beyond 18year old, 31 (40%) had only one sexual partner and 35 (40%) two; 18 (23%) had a previous episode of pelvic inflammatory disease (PID) and 30 (39%) pain and/or thickened adnexae. CONCLUSIONS: Most patients with infertility due to salpingitis do not present risk factors for PID or previous PID episodes. Diagnosis was done by infertility sequelae.